Mutation analysis in individual circulating tumor cells depicts intratumor heterogeneity in melanoma - Sementsov, Mark; Ott, Leonie; Kött, Julian; Sartori, Alexander; Lusque, Amelie; Degenhardt, Sarah; Segier, Bertille; Heidrich, Isabel; Volkmer, Beate; Greinert, Rüdiger; Mohr, Peter; Simon, Ronald; et al. (EMBO molecular medicine, 2024)
Circulating tumor DNA (ctDNA) is the cornerstone of liquid biopsy diagnostics, revealing clinically relevant genomic aberrations from blood of cancer patients. Genomic analysis of single circulating tumor cells (CTCs) could provide additional insights into intra-patient heterogeneity, but it requires whole-genome amplification (WGA) of DNA, which might introduce bias. Here, we describe a novel approach based on mass spectrometry for mutation detection from individual CTCs not requiring WGA and complex bioinformatics pipelines. After establishment of our protocol on tumor cell line-derived single cells, it was validated on CTCs of 33 metastatic melanoma patients and the mutations were compared to those obtained from tumor tissue and ctDNA. Although concordance with tumor tissue was superior for ctDNA over CTC analysis, a larger number of mutations were found within CTCs compared to ctDNA (p = 0.039), including mutations in melanoma driver genes, or those associated with resistance to therapy or metastasis. Thus, our results demonstrate proof-of-principle data that CTC analysis can provide clinically relevant genomic information that is not redundant to tumor tissue or ctDNA analysis.